The affordance-actualization process of predictive analytics: Towards a configurational framework of a predictive policing system - Godé, Cécile; Brion, Sébastien (Technological forecasting & social change, 2024)
Predictive analytics are changing the way people interact with technology, and therefore empirical studies on interaction processes between predictive analytics and users in the organizational context are needed. Drawing on Affordance Actualization Theory (AAT), this article addresses this gap by exploring how affordances of predictive analytics are actualized. Focusing on a French predictive policing system, it examines the affordance-use-actualization process developed by police officers as they interact with the system to achieve professional goals. We conducted an in-depth empirical study, followed by qualitative content analysis of triangulated datasets (twelve interviews, focused observations and archival data) and a FsQCA survey of 69 effective users. After identifying two affordances and five uses, our findings lead to a configurational framework showing how affordances of the predictive policing system are actualized through patterns of uses. This article contributes to AAT by revealing two distinct attributes of patterns of uses: equifinality (multiple patterns of uses actualize the same affordance) and polyfinality (a single pattern of uses actualizes multiple affordances). It also shows the benefits of using FsQCA methods to investigate the affordance-pattern of uses-actualization process. Finally, this article encourages practitioners to navigate complex and unforeseen processes that emerge from open-ended interactions with predictive analytics. •Explores the actualization process of predictive analytics affordances•Empirical study of predictive policing based on qualitative and FsQCA analysis•“Pattern of uses” concept supports the configurational nature of the affordance actualization process.•Extends Affordance Actualization Theory (AAT) by identifying patterns of uses having equifinal and polyfinal attributes